Why have we embraced minimally invasive surgery and ignored enhanced recovery after surgery? - Nanavati, Aditya J (J Minim Access Surg, 2016)
There has been a lot of enthusiasm about minimally invasive surgery (MIS) in the surgical community in recent times. Some of the main reasons for this are an unmatched appeal to patients, doctors and healthcare systems alike. Push from the industry also serves as an important reason for its popularity. 'Enhanced recovery after surgery' (ERAS) is a programme of implementing multimodal interventions in the perioperative period to promote faster recovery. Even though MIS is an important component of ERAS protocols, the latter has not seen the reception the former has received. In this article, the authors present their personal viewpoint on the matter. The authors intend to highlight issues surrounding an increasing emphasis on MIS and to caution against the MIS operative technique superseding comprehensive perioperative care.